Management Of Quality In Madrasah Education Based On Religious Moderation and Inclusive Education In Indonesia - Wahib, Abd.; Mohammad Zaini; Asnawan, Asnawan (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2023)
This paper is a paper that raises the theme of quality management in madrasah education based on religious moderation and inclusion, in this paper there are three questions, first, what is the concept of quality management, in madrasah education? Second, what is the concept of religious moderation which is inclusive in madrasah education? and third, how is quality management in madrasah education based on religious moderation and inclusion? f? by using a content analysis approach to explain the concept of quality management in madrasah education based on religious moderation and inclusion in Indonesia, the results of this paper are first to know the quality management of madrasah education